EEG and qEEG in psychiatry - Xia, L. (CRC Press, 2014)
Conventional EEG techniques are based on visual inspection of patterns from EEG records. This involves observation of changes in wave shapes, frequencies, and transitions of states that may not be found in healthy subjects. During the last few years, more robust techniques based on signal digitization and processing have been proposed, including quantitative electroencephalography (qEEG). Â© 2015 by Taylor & Francis Group, LLC.